Integrative Groundwater Studies in a Small-Scale Urban Area: Case Study from the Municipality of Penafiel (NW Portugal) - Freitas, Liliana (2022)
The occurrence of groundwater in urban hard rock areas is mostly controlled by secondary permeability caused by the fracturing degree and weathering grade. Vulnerability GIS-mapping, monitoring, and infiltration/recharge of water resources, and the delineation of the environmental protective background are key issues in evaluating, planning, managing, and decision-making for urban water systems. A small-scale urban area in Penafiel City was used as a case study. Historical and current scenarios were compared using hydrogeological GIS-based modelling. Water sources and potential contamination sources were mapped around the study area. Groundwater is mainly acidic, with a low mineralization and a Cl-Na to Cl-SO4-Na or Cl-Ca to Cl-SO4-Ca hydrogeochemical facies. Considering potential contamination sources, the moderate and the moderate-high classes dominate the area. The combined approach of the vulnerability indexes suggests that most of the area has a low to moderate vulnerability to contamination. The Infiltration Potential Index in urban areas (IPI-urban) indicates the prevalence of a low to moderate infiltration. Groundwater recharge evaluation indicates values < 2.3 mm/year and <60 mm/year for summer and winter scenarios, respectively. Finally, the investigation addresses insights for decision-makers for the appropriate planning and sustainable management of groundwater resources in small-scale urban areas.